Retrospection: genesis and durability of post‑war polychromes of tenement houses in the Old Market Square in Poznań - Łubowski, Andrzej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The article presents the artist's and researcher's own artistic experiences related to the implementation of painting decorations of tenement houses at the Old Market Square in Poznań. These are the works created in 1986, 1994 and 1997. The first project was a consequence of quite unexpected incorporation of the polychrome of the tenement houses at the Old Market Square in Poznań. It was about 30 years, after World War II, when the polychrome on the reconstructed tenement houses was created. There was a need to restore the painting decorations by Edmund Łubowski on a tenement house at 39 Stary Rynek and the sgraffito by Józef Flieger at 99 Stary Rynek. The situation was a consequence of such advanced destruction that the works could not undergo further conservation processes. Due to the fact that the authors were then still alive, it was possible to consult the reconstruction process. In 1994, the author received another proposal to make, according to his own design, a new painting decoration, made in the wet fresco technique, on a tenement house at 66 Stary Rynek. Later, in 2010, the restoration work was conducted in consultation with the author. In 1997, a painting decoration was designed on the tenement house at 3 Paderewskiego Street, close to the urban interior of the Old Market Square. Based on the project, painting decorations were made in the silicate technique. The artist's experience, drawn from the aforementioned works, has become the subject of qualitative research that correlates the passage of time and the type of wall painting techniques used as well as other technical conditions with artistic issues.